A prairie tragedy [electronic resource] : the fate of Thomas Simpson, the arctic explorer : read before the Historical and Scientific Society of Manitoba (Transaction no. 26 [i.e. 27]) - McArthur, Alexander, 1842-1887; Historical and Scientific Society of Manitoba. (Winnipeg : G.C. Mortimore, 1887)
Cover title. Caption title: A tragedy of the plains : the fate of Thomas Simpson, the arctic explorer. Electronic reproduction. Mode of access: Internet. 44